Fracmemristor chaotic oscillator with multistable and antimonotonicity properties - Haikong Lu; Jiri Petrzela; Tomas Gotthans; Karthikeyan Rajagopal; Sajad Jafari; Iqtadar Hussain (Journal of Advanced Research, 2020)
Memristor is a non-linear circuit element in which voltage-current relationship is determined by the previous values of the voltage and current, generally the history of the circuit. The nonlinearity in this component can be considered as a fractional-order form, which yields a fractional memristor (fracmemristor). In this paper, a fractional-order memristor in a chaotic oscillator is applied, while the other electronic elements are of integer order. The fractional-order range is determined in a way that the circuit has chaotic solutions. Also, the statistical and dynamical features of this circuit are analyzed. Tools like Lyapunov exponents and bifurcation diagram show the existence of multistability and antimonotonicity, two less common properties in chaotic circuits.